Benefits of flu vaccination for persons with diabetes mellitus: A review. Issue 38 (12th September 2017) - Goeijenbier, M.; van Sloten, T.T.; Slobbe, L.; Mathieu, C.; van Genderen, P.; Beyer, Walter E.P.; Osterhaus, Albert D.M.E.
Abstract: Diabetes mellitus imposes a significant and increasing burden on society, with major consequences for human health, welfare and the economy worldwide. Persons with diabetes mellitus are at increased risk of developing severe complications after influenza virus infection and guidelines advise vaccination. The present evidence for influenza vaccine effectiveness in persons with diabetes mellitus is mainly based on observational studies with clinical endpoints like hospitalization and death, indicating a beneficial reduction of morbidity and mortality. Further supportive evidence comes from serological studies, in which persons with diabetes mellitus usually develop similar antibody levels after vaccination as healthy people. Observational studies may be prone to selection bias, and serological studies may not completely mirror vaccine effectiveness in the field. Although more controlled trials in persons with diabetes mellitus with laboratory-confirmed, influenza-specific outcomes would be desirable to better estimate the effect of vaccination, the currently available data justify routine influenza vaccination in persons with diabetes mellitus. As in this risk group, the use of influenza vaccine is far below target worldwide, efforts should be made to increase vaccination coverage.